Tables of Declination from Ptolemy to Regiomontanus - Goldstein, Bernard R.; Chabás, José (Aestimatio, 2024)
The inclination of the path of the Sun in the sky with respect to the celestial equator, that is, the obliquity of the ecliptic, has been a major concern for astronomers since Antiquity. Many of them adopted values for it that departed from those of their predecessors and hardly any were the result of observation. Solar declination depends strictly on the obliquity, and many tables for determining solar positions were compiled during the Middle Ages. In this paper, we examine several of them, particularly those by Abraham ibn Ezra, Giovanni Bianchini, and Regiomontanus, the last two associated with tables for the conversion of ecliptic to equatorial coordinates.